TCO Optimization in Si Heterojunction Solar Cells on p-type Wafers with n-SiOx Emitter. (December 2015) - Izzi, M.; Tucci, M.; Serenelli, L.; Mangiapane, P.; Salza, E.; Chierchia, R.; Noce, M. Della; Usatii, I.; Bobeico, E.; Lancellotti, L.; Mercaldo, L.V.; Veneri, P. Delli
Abstract: Silicon heterojunction solar cells have largely demonstrated their suitability to reach high efficiencies. We have here focused on p-type c-Si wafers as absorber, considering that they share more than 90% of the solar cell market. To overcome some of the issues encountered in the conventional (n)a-Si:H/(p)c-Si configuration, we have implemented a mixed phase n-type silicon oxide (n-SiOx ) emitter in order to gain from the wider bandgap and lower activation energy of this material with respect to (n)a-Si:H. The workfunction of the transparent conductive oxide layer (WTCO ) plays also a key role, as it may induce an unfavourable band bending at the interface with the emitter. We have here focused on AZO, a promising alternative to ITO. Different layers with varying WTCO were prepared, by changing relevant deposition parameters, and were tested into solar cells. The experimental results have been explained with the aid of numerical simulations. Finally, for the n-SiOx /(p)c-Si heterojunction with optimized WTCO a potential conversion efficiency well over 23% has been estimated.